Association between genetic polymorphisms of cadherin 23 and noise-induced hearing loss: a meta-analysis - Zhi-Dan Wu; Jun-Qi Lu; Wen-Jing Du; Shan Wu (Taylor & Francis Group, 2022)
Background NIHL is one of the most common occupational diseases induced by gene-environment interaction. The CDH23 gene is a candidate gene related to NIHL susceptibility. However, the relationship between CDH23 gene and NIHL is still inconclusive. Aim To clarify the association between CDH23 gene and NIHL, a meta-analysis was performed. Subjects and methods A search in MEDLINE, PubMed, Web of Science, EBSCO, China National Knowledge Infrastructure (CNKI), and Wanfang Data was implemented to collect data. Results and conclusions Six studies were eventually included and all the subjects were Chinese. The results showed that rs1227051, rs1227049, and rs3752752 were not associated with NIHL susceptibility under five genetic models. But rs3802711 reduced the risk of NIHL under the recessive model, and the BB genotype and B allele of rs3802711 were significantly linked to NIHL under recessive, super-dominant, homozygote, and allele genetic models when stratified by the HWE result. Moreover, when not conform to HWE, the BB + AB genotypes and B allele of Exon7 in dominant, super-dominant, homozygote, and allele genetic model increased the risk of NIHL. CDH23 may be a potential gene marker for the prevention and early screening of NIHL in Chinese. Further large and well-designed studies are needed to confirm this association.